Lima bean (Phaseolus lunatus) seed coat phaseolin is detrimental to the cowpea weevil (Callosobruchus maculatus) - Moraes,R.A. (2000)
The presence of phaseolin (a vicilin-like 7S storage globulin) peptides in the seed coat of the legume Phaseolus lunatus L. (lima bean) was demonstrated by N-terminal amino acid sequencing. Utilizing an artificial seed system assay we showed that phaseolin, isolated from both cotyledon and testa tissues of P. lunatus, is detrimental to the nonhost bruchid Callosobruchus maculatus (F) (cowpea weevil) with ED50 of 1.7 and 3.5%, respectively. The level of phaseolin in the seed coat (16.7%) was found to be sufficient to deter larval development of this bruchid. The expression of a C. maculatus-detrimental protein in the testa of nonhost seeds suggests that the protein may have played a significant role in the evolutionary adaptation of bruchids to legume seeds.